Barriers to formal police–community corrections partnerships: A comparison of police chiefs and chief probation/parole officers' perceptions. (June 2017) - Kim, Bitna; Matz, Adam K; Gerber, Jurg
Although there has been continuing and increasingly intensive interest in police–community corrections partnerships over the past two decades, recent studies have found that the majority of partnerships remain informal endeavors. Little is known about the reasons why police and community corrections agencies do not formalize partnerships. To address this gap in knowledge, we collected state-wide survey data from police chiefs and chief probation/parole officers in Pennsylvania regarding barriers to partnerships as well as interest in new partnership opportunities. The results revealed that for both police and probation/parole agencies, the most common reason for nonparticipation was that they have not been approached by the respective agencies. A lack of funding resources was the second most common barrier for both agencies. The so-called stalking horse concern was another significant barrier for probation/parole agencies, but it was not significant for police agencies. Regarding favorability to future partnerships, most respondents were interested in formal partnerships, but only a few agency representatives noted that they were actively seeking out opportunities to partner. The implications for policies, training, and future research are discussed.